2013
DOI: 10.1002/stem.1392
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Sox2 for the Establishment and Maintenance of the Germ Cell Line

Abstract: Sox2 is a pluripotency-conferring gene expressed in primordial germ cells (PGCs) and postnatal oocytes, but the role it plays during germ cell development and early embryogenesis is unknown. Since Sox2 ablation causes early embryonic lethality shortly after blastocyst implantation, we generated mice bearing Sox2-conditional deletion in germ cells at different stages of their development through the Cre/loxP recombination system. Embryos lacking Sox2 in PGCs show a dramatic decrease of germ cell numbers at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
107
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 59 publications
(90 reference statements)
10
107
0
1
Order By: Relevance
“…Embryos lacking Sox2 in PGCs showed a dramatic decrease of germ cell numbers at the time of their specification. At later stages, we found that SOX2 is strictly required for PGC proliferation (Campolo et al, 2013). We have also found that SOX2 stimulates Kit expression in PGCs and binds to discrete transcriptional regulatory sequences of this gene, which is known to be essential for PGCs survival and proliferation.…”
Section: Transcription Factors Controlling Kit Expression In the Germmentioning
confidence: 58%
See 2 more Smart Citations
“…Embryos lacking Sox2 in PGCs showed a dramatic decrease of germ cell numbers at the time of their specification. At later stages, we found that SOX2 is strictly required for PGC proliferation (Campolo et al, 2013). We have also found that SOX2 stimulates Kit expression in PGCs and binds to discrete transcriptional regulatory sequences of this gene, which is known to be essential for PGCs survival and proliferation.…”
Section: Transcription Factors Controlling Kit Expression In the Germmentioning
confidence: 58%
“…Interestingly, ChIP analysis showed that these regulatory regions are present within the Kit first intron, which, as stated above, is essential for Kit expression in PGCs. On the contrary Sox2 conditional deletion in meiotic oocytes does not impair postnatal oogenesis and early embryogenesis, indicating that it is not essential for oocyte maturation nor for zygotic development, and inferring that SOX2 is not involved in the regaining of Kit expression during postnatal oogenesis (Campolo et al, 2013).…”
Section: Transcription Factors Controlling Kit Expression In the Germmentioning
confidence: 92%
See 1 more Smart Citation
“…Notably, PGCs show dormant totipotency, although PGCs are monopotential cells for the generation of gametes. Nonetheless, PGCs and PSCs remain closely related: both cell types share the expression of several pluripotency-associated transcription factors (9)(10)(11)(12), and PGCs are easily reprogrammed into naïve PSCs, designated embryonic germ cells (EGCs), in culture (13,14). Therefore, the intrinsic mechanisms that control the distinct developmental potential of these two cell types are of great interest.…”
mentioning
confidence: 99%
“…Sox2 is a transcription factor functionally important for normal stem cells, including pluripotent and tissue-specific stem cell types (8)(9)(10)(11)(12). In the nervous system, Sox2 is active in NSCs and progenitors of the embryo and adult (8,12).…”
Section: Introductionmentioning
confidence: 99%